INDUSTRIAL TEST OF A/D CONVERTERS IN LABVIEW - Raze, Stephane; Dallet, Dominique; Marchegay, Phillipe (International Journal of Computing, 2014)
An industrial test bench for Analog-to-Digital Converters (ADC) is presented in this article. The bench hardware has been composed with known devices of instrumentation. This hardware had been identified from ADCs under test requirements. All of hardware is handled by a software written in LabVIEW development system.